2011
DOI: 10.2165/11586870-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy, Aging and Potential Drug-Drug Interactions in Outpatients in Taiwan

Abstract: This study showed that approximately one-quarter of 81,650 outpatients who visited a medical centre in Taiwan over a period of 3 months in 2004 had potential DDIs. We observed independent increases in potential DDIs per person in association with aging and increasing number of prescribed drugs. Furthermore, a significant interaction between these two factors was observed: the effect of aging on the prevalence of potential DDIs increased as the number of prescribed drugs increased. Potential DDIs in outpatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
58
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 29 publications
11
58
1
2
Order By: Relevance
“…Caffeine + Phenylephrine 2 A retrospective study by Lin et al 11 in outpatients in Taiwan emphasis that polypharmacy increases the risk of DDIs. In present study, maximum number of patients prescribed two drugs per prescription.…”
Section: Decrease Sedative Effectmentioning
confidence: 99%
“…Caffeine + Phenylephrine 2 A retrospective study by Lin et al 11 in outpatients in Taiwan emphasis that polypharmacy increases the risk of DDIs. In present study, maximum number of patients prescribed two drugs per prescription.…”
Section: Decrease Sedative Effectmentioning
confidence: 99%
“…For each patient, the number drugs prescribed and ATC code classification of drug therapy were analyzed as drug therapy characteristics. Selected predictor factors were chosen in accordance with the results of previous studies [22,25,28,31].…”
Section: Predictors Of Potential Ddismentioning
confidence: 99%
“…Additionally, the frequency study of potential DDIs at geriatric outpatient in 6 European countries showed that there were differences in frequency, as well as in the type of potential DDIs [23]. By study of predictors to DDIs was also observed variability, those which are patient characteristics as well as those which are therapy characteristics [20][21][22][24][25][26][27][28][29][30][31][32]. Differences in healthcare settings, registered and reimbursed pharmaceutical specialities can contribute to different utilization patterns of prescription drugs.…”
mentioning
confidence: 99%
“…7 Polypharmacy, defined as the concomitant use of multiple medications (e.g., customarily five or more medications), has been associated with increasing age 8,9 and with an increased risk of adverse drug reactions, increased hospitalizations, poor adherence, inappropriate drugs, falls and fractures, and drug-drug interactions. [10][11][12][13][14][15] The risk for drug-drug interactions may be particularly increased among the aging population of HIV-infected adults due to treatments for multiple comorbidities in this population [16][17][18][19] as well as the concomitant use of ARV therapy. Among the antiretroviral classes, non-nucleoside reverse transcriptase inhibitors (NNRTIs) and protease inhibitors (PIs) are major substrates as well as both inhibitors and inducers of the cytochrome P450 (CYP) enzyme system.…”
Section: Introductionmentioning
confidence: 99%
“…Although polypharmacy and its impact on drug-drug interactions has been well-described in various studies from the general population, 13,14,[25][26][27][28][29][30][31][32][33] there are limited data among the aging population of HIV-infected adults. 2,[34][35][36] Therefore, we sought to examine the potential impact of polypharmacy on the risk of drug-drug interactions between ARVs and other medications (ARV/non-ARV interactions) in a US cohort of HIV-infected adults seen in the outpatient setting.…”
Section: Introductionmentioning
confidence: 99%